PERANCANGAN SISTEM INFORMASI PERPUSTAKAAN DIGITAL BERBASIS WEBSITE MENGGUNAKAN METODE WATERFALL DI JURUSAN INFORMATIKA UNIVERSITAS SILIWANGI - Lukmana, Hen Hen; Alhusaini, Muhamad; Purwayoga, Vega (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2023)
The COVID-19 pandemic that occurred at the end of 2019 has accelerated the application and use of technology in universities. Various academic activities, such as learning, final project work, and UTS and UAS, were completed online. But unfortunately, supporting facilities such as digital libraries are needed as a source of reference and information that can store various material needs such as ebooks and modules that can be used for the learning process and can be accessed anywhere and anytime. This is the basis for designing the Digital Library Information System to make it easier for lecturers and students to find the books and modules they need. This library information system is web-based and made with HTML, CSS, Javascript, PHP, and MySQL programming languages. The method used in the development of this digital library information system is the waterfall method with the UML (Unified Modeling Language) software approach. With the Informatics Digital Library, it is hoped that it can help students and lecturers find various references and information for the learning process.